Optical Properties of Manufactured Mirrors Using DC Plasma Magnetron Sputtering Technique - Sadeq, Hussien Ala’a; Yaseen, Waleed Ibrahim (Iraqi Journal of Science, 2022)
This paper defines a method for sputtering high strength, extremely conductive silver mirrors on glass substrates at temperatures ranging from 20o to 22o C. The silver coated layer thicknesses in this work ranges from 7.5 to 16.1 nm using sputtering time from 10 to 30 min at power 25 W, 13.7 to 29.2 nm for time 10 to 30 min at 50 W, 15.7 to 26.4 nm for time 10 to 30 min at 75 W and 13.8 to 31.1 nm for time 10 to 30 min at 100 W. The optimum values of pressure and electrode gape for plasma sputtering system are 0.1 mbar and 5 cm respectively. The effect of DC sputtering power, sputtering duration or (sputtering time), and thickness on optical properties was investigated using an ultraviolet-visible spectrophotometer. The ultraviolet absorption of all coated layers was high, while the visible absorption was low. The transmittance is decrease with increase sputtering time and sputtering power. Highest values of reflection in visible region at 100 W and 20, 25 and 30 min are 46% to 97%. High value of band gap at 100 and 30 min while lower value at 25 W and 10 min.